Efficient Treatment of Wood Vinegar via Microbial Electrolysis Cell With the Anode of Different Pyrolysis Biochars - Shen, Ruixia; Zhao, Lixin; Yao, Zonglu; Feng, Jing; Jing, Yong; Watson, Jamison (Frontiers in Energy Research, 2020)
Microbial electrolysis cell (MEC) had a good performance during the treatment of bio-refractory wastewater. This study focused on wood vinegar (from biomass pyrolysis) treatment via MECs with biochar anode. The results indicated that MECs with coconut shell biochar as the anode had an obvious beneficial effect for treating wood vinegar. When wood vinegar was used as the substrate of MECs, COD removal reached up to 71.4%, and effluent COD was 359.0 mg COD/L. GC-MS analysis showed that furfurals present in the wood vinegar were thoroughly degraded after MEC treatment. One interesting finding is that hydrocarbons accounted for a large portion of the compounds in the effluent, which may be the comprehensive result of complex organic reactions, including decarboxylation reactions, dehydration reaction, etc. The dominant microbial populations in MEC with biochar anode mainly included Geobacter, Macellibacteroides, Oscillibacter, Sedimentibacter, Comamonas and Lachnoclostridium. In particular, Lachnoclostridium (3.34%), a new family of exoelectrogens, may be correlated with the degradation of wood vinegar. This study demonstrated that pyrolysis biochar could be incorporated as a high-efficiency MEC anode material, and MECs with the inclusion of biochar could provide a feasible way for the treatment of recalcitrant wood vinegar.